The old rules of marketing are dead 6 new rules to reinvent your brand & reignite your business - Pearson, Timothy R. (McGraw-Hill, 2011)
Argues that the new methods of human communication require a new perspective on marketing, outlining a plan to reinvent the marketing industry by applying quantitative data and providing leadership in a new business landscape.